Prevalence of Leishmania RNA virus in Leishmania parasites in patients with tegumentary leishmaniasis: A systematic review and meta-analysis. - Endalew Yizengaw Shita; Endalkachew Nibret Semegn; Gizachew Yismaw Wubetu; Abaineh Munshea Abitew; Bizuayehu Gashaw Andualem; Mekuanint Geta Alemneh (Public Library of Science (PLoS), 2022)
Background Cutaneous leishmaniasis is caused by different protozoan parasites of the genus Leishmania. Leishmania RNA virus (LRV) was identified as the first Leishmania infecting virus in 1998. Different studies showed the presence and role of the LRV in Leishmania parasites causing cutaneous leishmaniasis (CL). However, there is limited data on the pooled prevalence of LRV in Leishmania parasites causing CL. Therefore, the aim of this systematic review and meta-analysis was to determine the pooled prevalence of LRV in Leishmania parasite isolates and/or lesion biopsies in patients with CL from the available literature globally. Methodology We retrieved the studies from different electronic databases. The studies were screened and identified based on the inclusion and exclusion criteria. We excluded studies exclusively done in experimental animals and in vitro studies. The review was conducted in line with PRISMA guidelines. The meta-analysis was performed with Stata software version 14 with metan command. The forest plot with random-effect model was used to estimate the pooled prevalence with 95% confidence interval. Inverse variance index (I2) was used to assess the heterogeneity among the included articles. Principal findings A total of 1215 samples from 25 studies were included. Of these, 40.1% (487/1215) were positive for LRV. The overall pooled prevalence of LRV globally was 37.22% (95% CI: 27.54% - 46.90%). The pooled prevalence of LRV in the New World (NW) and Old World (OW) regions was 34.18% and 45.77%, respectively. Leishmania guyanensis, L. braziliensis, L. major, and L. tropica were the most studied species for the detection of LRV. The prevalence of LRV from Leishmania isolates and lesion biopsies was 42.9% (349/813) and 34.3% (138/402), respectively. Conclusion This systematic study revealed that there is high prevalence of LRV in Leishmania parasites isolated from patients with CL. More comprehensive studies would be required to investigate the presence of the LRV in other Leishmania species such as L. aethiopica to fully understand the role of LRV in different clinical manifestations and disease pathology presented in CL patients.